Local Government Financial Performance: Challenges and Opportunities - Abdullah, Amnatia R; Hulopi, Titi Umi Kalsum; Hartoyo, Abdulrival; Ibrahim, Ely; Sanaba, Risna (West Science Interdisciplinary Studies, 2024)
The financial performance of local governments is an important indicator in assessing the efficiency and effectiveness of public resource management. This article discusses the challenges faced by local governments in improving financial performance, including issues of transparency, accountability, and suboptimal budget management. In addition, this study also identifies opportunities that can be utilized, such as the application of information technology in financial reporting systems and increasing human resource capacity. Using descriptive analysis and literature studies, the results of the study indicate that despite many challenges, there are a number of strategies that can be implemented to improve the financial performance of local governments, which in turn can support sustainable development and community welfare. This study is expected to provide insight for policy makers and stakeholders in formulating more effective policies.
Keywords: Financial Performance; Local Government; Challenges; Opportunities in Budget Management